2019
DOI: 10.1111/asj.13274
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Wakame seaweed (Undaria pinnatifida) stalk to animal feed enhances immune response and improves intestinal microflora in pigs

Abstract: This study was conducted to evaluate the effects of supplementation of Wakame seaweed stalks on the immunity and intestinal microflora of pigs. Three separate experiments were performed: Relatively young (start at 20–30 kg; Experiments 1 and 2) and fattening period (70 kg; Experiment 3). All pigs (including the control group) were fed the same commercial feed, free from antibiotic additives, but in the feed for the treatment groups, 1% seaweed powder was added. There were no group differences observed in daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…The direct addition of seaweed biomass into animal feed can also improve the livestock's health and growth and the subsequent meat quality. Supplementing Undaria pinnatifida into swine feed improved the total immune response via regulating the toll-like receptor genes and cytokines, in addition to modulating the intestinal microflora to promote the beneficial Lactobacillus bacteria and reduce Escherichia coli consortium (Shimazu et al 2019 ). The effects of feeding seaweeds to various animal species will be discussed in depth.…”
Section: Uses Of Seaweed In Livestock Feedmentioning
confidence: 99%
“…The direct addition of seaweed biomass into animal feed can also improve the livestock's health and growth and the subsequent meat quality. Supplementing Undaria pinnatifida into swine feed improved the total immune response via regulating the toll-like receptor genes and cytokines, in addition to modulating the intestinal microflora to promote the beneficial Lactobacillus bacteria and reduce Escherichia coli consortium (Shimazu et al 2019 ). The effects of feeding seaweeds to various animal species will be discussed in depth.…”
Section: Uses Of Seaweed In Livestock Feedmentioning
confidence: 99%
“…Seaweed supplementation in livestock, poultry, and aquaculture feed has been practiced for decades and has shown tremendous improvements in animal health and meat quality and in reducing methane emissions of cattles [ 30 ]. For instance, the addition of brown algae Undaria pinnatifida and Ascophyllum nodosum in the diet of pigs and sheep improves the animals’ intestinal health, while the incorporation of red algae Eucheuma denticulatum in fishmeal improves the meat quality of Japanese flounders by increasing the amount of omega-3 fatty acids in the muscles [ 31 , 32 , 33 ]. Seaweed extract is commercialized as plant biostimulants as well.…”
Section: Seaweed Uses: a Commercial Perspectivementioning
confidence: 99%
“…Additionally, bamboo vinegar powder has positive effects on promoting the abundance of Lactobacillus and Thalassospira and on inhibiting Streptococcus and Prevotella growth ( 98 ). 1% Wakame seaweed powder maybe alter intestinal microflora preferentially, namely, which are observed that an increase in Lactobacillus and a decrease of Escherichia coli to improve the gut health and immunity of pigs ( 99 ). Feeding the diet supplemented with dried Jerusalem artichoke (DJA) tubers, as a source of inulin-type fructans, affects the microbiota activity in the large intestine by decreasing proteolytic fermentation and detrimental bacterial enzyme activity.…”
Section: Pharmacological Applications Of Phytochemicals In Pig Productionmentioning
confidence: 99%